Horror in the East - Rees, Laurence 1957-.; West, Samuel; Elston, Paul.; Barret, Sean.; Wheeler, Charles; Gibson, Jeremy; Fielder, Mark.; British Broadcasting Corporation. Television Service; Arts and Entertainment Network (London BBC Worldwide Limited, 2005)
Turning against the west explains why the Japanese Army turned from being a westernized, "civilized", military which treated its prisoners well during during World War I into the brutal military which fought aganist the allies in World War II; Death before surrender- The Allies celebrated victory over Japan on August 15, 1945, Japan enjoyed a series of early victories from its entry in the war at Pearl Harbor in December 1941, followed by the conquest to Hong Kong, Burma, the Philippines, Malaysia and Borneo. On August 6, 1945, the US dropped the first atomic bomb on Hiroshima and three days later a second on Nagasaki. With that and the Soviet declaration of war on August 8, the Japanese were forcedinto a surrender that was virtually unconditional. Kamikaze, which means "Divine Wind" in Japanese, was Japan's last attempt to balance the ever increasing technological and material advantage of the American forces advancing to Japan; The forgotten volunteers- At the outbreak of World War II, the Indian army numbered 205,000 men. Later during World War II, the Indian armybecame the largest all-volunteer force in the history rising to over 2.5 million men in size. These forces included tank, artillery and airborne forces. Indian soldiers won 30 Victoria Crosses during the second World War. India was also made into a nation to produce essential goods such as food and uniforms. Ores were mined to support the war much to the consternation of Indians. Pre-Independence India provided the largest"volunteer" force (2.5 million) of any nation during World War II; Burma: the forgotten war- Many Burmese, resenting the Britain's hold over their country which went all the way back to the nineteenth century, cooperated when the Japanese invaded in December 1941. The Japanese saw Burma as a stepping-stone to India as well as protection for their troops fighting in the Malayan peninsula and in Singapore. British attempts to get Burma back in 1942 and 1943 were unsuccessful. The Japanese gave some independence to Burma in 1943, but forced local workers, along with prisoners of war, to build the Burma Railway. Over 100,000, a third of the labourers, died from overwork, malnutrition and disease.
Disc 1. Turning against the west / written and produced by Laurence Rees ; narrator, Samuel West (46 min., 57 sec.) ; Death before surrender / narrator, Samuel West (48 min., 7 sec.) -- Disc 2. The forgotten volunteers / written and directed by Paul Elston ; narrator: Sean Barrett (46 min., 51 sec.) ; Burma : the forgotten wars / presented by Charles Wheeler ; executive producer, Jeremy Gibson ; producer, Mark Fielder (58 min., 29 sec.)
Summary from container.
DVD
In Chinese or English ; with English and Chinese subtitles.
Keywords: Sino-Japanese War, 1937-1945 -- Atrocities; Sino-Japanese War 1937-1945 -- Campaigns; World War, 1939-1945 -- Atrocities; World War, 1939-1945 -- Campaigns -- Southeast Asia; Documentary films